RELEVANCE OF VALUES IN PO'O RITUAL WITH VALUES EDUCATION IN LEARNING IPS IN ELEMENTARY SCHOOLS - Felix Welu (Sean Institute, 2023)
The objectives of this study were: 1) To find out the process of implementing the Po'o traditional ritual in the Liselobora Village community, 2) To find out the cultural values of local wisdom contained in the Po'o traditional ritual and 3) To find out the implementation of the values local wisdom culture in the Po'o ritual for character building in social studies in elementary school. The method used in this study is a qualitative method, the data sources used in this research are primary data and secondary data. Data collection techniques consist of observation techniques, interviews, documentation and photographs. Based on the results of the study it can be concluded that Po'o comes from the language lio which means bamboo. The Po'o ritual is a traditional ceremony passed down by the ancestors and upheld by the Liselobora community and passed on to the next generation. Rituals carried out by the Liselobora community are carried out for one day and once a year. This ritual is performed to invoke Du'a Gheta Lulu Wula, Nggae Ghale Wena Tanah (God) and Embu Mamo (Ancestors) to fertilize the soil and start the planting season in a farming system. In the Po'o ceremony there are three values in it, namely: 1) Social values in Po'o are togetherness and brotherhood of the Liselowobora people, 2) Cultural values in this ritual are the preservation of cultural heritage from the ancestors of the Liselobora people and 3) Religious values in carrying out the Po'o ritual when offering offerings to Du'a Nggae, asks God to give him fertility and an abundance of crops. Character education for children is a process of character formation to have a positive impact on emotional, spiritual and personality development. The purpose of character education is to develop the conscience or affective potential of children as human beings and citizens who have character values, develop habits and behavior of children that are commendable and consistent.